Exercising to Improve Movement Quality: Why and How. (May 2021) - Bennett, Hunter; Arnold, John; Davison, Kade
Abstract : Training to improve movement quality is a worthwhile pursuit for exercise professionals as it has the capacity to improve training safety and effectiveness, while also increasing performance outcomes. Apply It!: Exercise interventions targeting improvements in movement quality can increase training safety and effectiveness. Movement quality–specific training can cause improvements in functionally relevant performance outcomes in a way that may be perceived as easier than traditional training interventions. Assessing movement quality before prescribing exercise can highlight areas of training focus while identifying key exercises that your clients can perform safely.